Assessing the national capacity for disaster research response (DR2) within the NIEHS Environmental Health Sciences Core Centers - Nicole A. Errett; Erin N. Haynes; Nancy Wyland; Ali Everhart; Claire Pendergrast; Edith A. Parker (BMC, 2019)
Abstract Introduction Disaster research response (DR2) is necessary to answer scientific questions about the environmental health impacts of disasters and the effectiveness of response and recovery strategies. This research explores the preparedness and capacity of National Institute of Environmental Health Sciences (NIEHS) P30 Core Centers (CCs) to conduct DR2 and engage with communities in the context of disasters. Methods In early 2018, we conducted an online survey of CC Directors (n = 16, 69.5% response rate) to identify their DR2 relevant scientific assets, capabilities, and activities. Summary statistics were calculated. We also conducted in-depth, semi-structured interviews with 16 (69.5%) CC Community Engagement Core directors to identify facilitators and barriers of DR2 community engagement. Interview notes were coded and thematically analyzed. Results Survey: While 56% of responding CCs reported prior participation in DR2 and preparedness to repurpose funding to support DR2, less than one third reported development of a disaster-specific data collection protocol, deployment plan, or concept of operations plan, participation in an exercise to test DR2 capacity, development of academic partnerships to conduct DR2, development of a process for fast-tracking institutional review board approvals for DR2, or maintenance of formal agreements with state, local, or community-based partner(s). A number of CCs reported developing or considering developing capacity in these areas. Barriers to, and tools and resources to enhance, CC engagement in DR2 were identified. Interviews: Four key components for community engaged DR2 were identified: pre-existing community relationships, responsive research that benefits communities, coordination among researchers, and coordination with community response partners. Several roles for, benefits of, and barriers to Community Engagement Rapid Response Teams (CERRT) were described. Conclusions CCs have significant scientific assets and community partnerships that can be leveraged for DR2; however, additional planning is necessary to ensure that these scientific assets and community partnerships are leveraged when disasters strike.